2011
DOI: 10.1017/s0022029911000021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dioxin exposure on several indices of blood redox status in lactating buffalo cows

Abstract: Dioxins are lipophilic compounds with a small molecular weight and are highly persistent, bioaccumulative and toxic. Dioxin detoxification is associated with an increased production of reactive oxygen species (ROS). In physiological conditions the body is protected against ROS and their toxic products by a wide range of antioxidant systems. We hypothesize that the imbalance between ROS production, associated with dioxin exposure, and the antioxidant defence capacity, may lead to oxidative stress, with conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(54 reference statements)
2
8
0
Order By: Relevance
“…These findings agree with the data previously obtained in buffalo cows (Spagnuolo et al, 2011), as well as in other laboratory species exposed to either 2,3,7,8 tetrachloro-dibenzo-p-dioxin (Stohs et al, 1984;Hassoun et al, 1998;Slezak et al, 2002) or to DL-PCBs (Lai et al, 2010), and support the hypothesis that the exposure to environmental pollutants, such as dioxins, severely impairs the blood antioxidant defence system. As expected, we found that the lower antioxidant capacity, observed in exposed cows, is associated with a significantly higher extent of oxidative modifications of protein and lipid.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings agree with the data previously obtained in buffalo cows (Spagnuolo et al, 2011), as well as in other laboratory species exposed to either 2,3,7,8 tetrachloro-dibenzo-p-dioxin (Stohs et al, 1984;Hassoun et al, 1998;Slezak et al, 2002) or to DL-PCBs (Lai et al, 2010), and support the hypothesis that the exposure to environmental pollutants, such as dioxins, severely impairs the blood antioxidant defence system. As expected, we found that the lower antioxidant capacity, observed in exposed cows, is associated with a significantly higher extent of oxidative modifications of protein and lipid.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings suggest that in cows a significant part of the plasma antioxidant capacity, as measured by Trolox Equivalent Capacity, might be accounted for by Asc, and support the hypothesis that circulating Asc plays a major role in preventing protein oxidative modifications induced by carbonyls, as previously reported for humans (Krajcovicova-Kudlackova et al, 2006) and buffalo cows (Spagnuolo et al, 2011). Asc is a well known scavenger of peroxynitrite, and SOD is an enzymatic antioxidant involved in the scavenging of superoxide (Beckman and Koppenol, 1996;Halliwell and Gutteridge, 2000).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Determination of antioxidants and lipid hydroperoxides. Plasma samples were processed for determination of Asc concentration as previously described (Spagnuolo et al, 2011), and analyzed by high performance liquid chromatography (HPLC) using an anion exchange column (Nucleosil 100-NH 2 , 5 μm, 250 × 4.6 mm i.d.). Ret and Toc levels were measured according to a published procedure (Spagnuolo et al, 2003), and analyzed by HPLC using a reverse phase C18 column (Nova-PAK C18, 4 μm, 125 × 2 mm i.d.).…”
Section: Methodsmentioning
confidence: 99%
“…The damaging action of ROS, if not counteracted or prevented by antioxidant defenses, causes cell death, tissue oxidative stress and organ ageing or failure (Halliwell and Gutteridge, 1999). Ascorbate (Asc), α-tocopherol (Toc) and retinol (Ret) are able to scavenge ROS and prevent oxidative damage, in the hydrophilic and lipophilic compartment and their concentration in plasma could be used as marker of oxidative stress (Spagnuolo et al, 2011). The concentration of protein-bound carbonyls (PC) and nitro-tyrosine (N-Tyr) in blood plasma, is also a reliable method to evaluate the extent of oxidative protein damage (Beal, 2002;Dalle-Donne et al, 2003) as N-Tyr and PC are considered markers of ROS-mediated protein oxidation (Berlett and Stadtman, 1997).…”
Section: Introductionmentioning
confidence: 99%